2021
DOI: 10.2337/dc21-0476
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Confocal Microscopy Predicts the Development of Diabetic Neuropathy: A Longitudinal Diagnostic Multinational Consortium Study

Abstract: OBJECTIVE Corneal nerve fiber length (CNFL) has been shown in research studies to identify diabetic peripheral neuropathy (DPN). In this longitudinal diagnostic study, we assessed the ability of CNFL to predict the development of DPN. RESEARCH DESIGN AND METHODS From a multinational cohort of 998 participants with type 1 and type 2 diabetes, we studied the subset of 261 participants who were free of DPN at baseline and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The primary endpoint will be the difference between the change over 12 months in corneal nerve fibre length (CNFL) determined using corneal confocal microscopy (CCM) in the benfotiamine group and the placebo group. CCM is currently the most suitable non-invasive instrument to assess early changes in small nerve fibre morphology in DSPN trials 20 21. A recent meta-analysis confirmed a reduction of CCM indices in patients with DSPN compared with individuals without DSPN 22.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The primary endpoint will be the difference between the change over 12 months in corneal nerve fibre length (CNFL) determined using corneal confocal microscopy (CCM) in the benfotiamine group and the placebo group. CCM is currently the most suitable non-invasive instrument to assess early changes in small nerve fibre morphology in DSPN trials 20 21. A recent meta-analysis confirmed a reduction of CCM indices in patients with DSPN compared with individuals without DSPN 22.…”
Section: Methods and Analysismentioning
confidence: 99%
“…CCM is currently the most suitable non-invasive instrument to assess early changes in small nerve fibre morphology in DSPN trials. 20…”
Section: Primary Endpointmentioning
confidence: 99%
“…Subsequent funding from the NIDDK enabled the establishment of an international consortium, which combined data from ~1000 patients with type 1 and type 2 diabetes and impaired glucose tolerance and showed that CCM has excellent diagnostic [ 12 , 13 ] and prognostic [ 14 ] value and could detect early nerve regeneration after simultaneous pancreas and kidney transplantation in patients with type 1 diabetes [ 15 , 16 ]. Age-adjusted normative values for CCM were established [ 17 ], and we showed that the severity of corneal nerve loss and associated risk factors are different for type 1 and type 2 diabetic patients [ 18 ].…”
Section: Ccm In Diabetic Neuropathymentioning
confidence: 99%
“…Corneal nerve loss also occurs in patients with painful sarcoid neuropathy [ 44 ], painful human immunodeficiency virus (HIV) neuropathy [ 45 ], chemotherapy-induced peripheral neuropathy, and fibromyalgia [ 46 ].…”
Section: Corneal Confocal Microscopy In Small Fiber Neuropathymentioning
confidence: 99%